Biodiversity and business: What do we know about biodiversity accountability? - Paola Vola; Lorenzo Gelmini (University American College Skopje, 2020)
The aim of this paper is to investigate the complex relationship between global business and biodiversity. Since business organizations impact biodiversity degradation and at the same time have to face the consequences of the loss of biodiversity, it seems necessary to further investigate the role played by business organizations in alleviating biodiversity loss (Reade, Goka, Thorp, Mitsuhata and Wasbauer, 2014). In order to study how business organizations comprise the topic of biodiversity in reality, this research primarily proposes a literature review on biodiversity in the field of accounting, management and organization. This assessment is significant being, as far as we know, one of the first systematic reviews of the literature on biodiversity and natural capital.
Keywords: 330; biodiversity; accounting; management; organization; accountability